An evaluation of the performance of the Hepatitis B surveillance system at Charlotte Maxeke Johannesburg Academic Hospital for 2017 –2018 - Kistan, Jesne (My University, 2021)
Background: Infection with Hepatitis B virus is a public health priority globally due the transmissible nature of the virus and the subsequent complications of Hepatitis B related disease. Public health surveillance systems are necessary to manage public health priorities such as Hepatitis B virus as these systems detect public health threats and inform public health actions. Surveillance systems need to be functioning appropriately to effectively inform public health responses. Therefore, it would important to assess the functioning of a surveillance system. Methods: We conducted a cross-sectional study of the performance of the attributes of the Hepatitis B virus surveillance system at Charlotte Maxeke Johannesburg Academic Hospital between 2017 –2018. We performed a retrospective record review of the completeness and timeliness of the Hepatitis B virus positive case notification. We further conducted a survey of the healthcare worker (doctors and infection prevention and control nurses) perceptions of the attributes (i.e. simplicity, acceptability, timeliness, flexibility and usefulness) of the HBV surveillance system. Results: Overall, 45.2% (n=238) of positive Hepatitis B virus cases were reported from Charlotte Maxeke Johannesburg Academic Hospital to the City of Johannesburg district office. Of 83 matched cases, 44.6% (n=37) of cases were found to be reported timeously. Health care workers (n=82) largely perceived the HBV surveillance system at CMJAH to be unacceptable (45.0%, n=36), untimely (37.8%, n=31) and not useful (74.1%, n=60). They were equivocal regarding the simplicity and flexibility of the surveillance system. Conclusion: Dysfunction of the HBV surveillance system directly impacts on South Africa’s ability to prevent infection with Hepatitis B virus and disease-related morbidity and mortality. Staff training, roll out of electronic reporting systems and routine feedback and monitoring of the HBV surveillance system could improve functioning of this system
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Public Health Medicine, 2021